X-ray absorption near-edge spectroscopy study of photoluminescent Ca2.955Sc2−xAlxSi3O12:Ce3+ green phosphors. Issue 3 (April 2015) - Wu, Yun-Fang; Chiou, Jau-Wern; Nien, Yung-Tang; Yeh, Chen-Lin; Chen, In-Gann; Lee, Jyh-Fu
Abstract: Al 3+ co-doped Ca2.955 Sc2 Si3 O12 :Ce 3+ green phosphors were systematically investigated using X-ray absorption near-edge spectroscopy (XANES) to understand the influence of Al 3+ incorporation on photoluminescence behavior. XANES analysis was used to confirm the doping site of Al atoms in the Ca2.955 Sc2 Si3 O12 :Ce 3+ host, the valence state of Ce atoms, the symmetry around Ca and Ce atoms, and the bonding modes of oxygen atoms with cation atoms in the as-prepared Ca2.955 Sc2− x Al x Si3 O12 :Ce 3+ (CSAS:Ce). XANES results indicate that Al 3+ occupies the Sc 3+ sites and stabilizes the crystal structure of the host material. Furthermore, Al 3+ can effectively inhibit the oxidization of Ce 3+ to Ce 4+, which enhances the photoluminescence of CSAS:Ce green phosphors.